RIMA-Dependent Nuclear Accumulation of IYO Triggers Auxin-Irreversible Cell Differentiation in Arabidopsis - Muñoz, Alfonso (2017)
The transcriptional regulator MINIYO (IYO) is essential and rate-limiting for initiating cell differentiation in Arabidopsis thaliana Moreover, IYO moves from the cytosol into the nucleus in cells at the meristem periphery, possibly triggering their differentiation. However, the genetic mechanisms controlling IYO nuclear accumulation were unknown, and the evidence that increased nuclear IYO levels trigger differentiation remained correlative. Searching for IYO interactors, we identified RPAP2 IYO Mate (RIMA), a homolog of yeast and human proteins linked to nuclear import of selective cargo. Knockdown of RIMA causes delayed onset of cell differentiation, phenocopying the effects of IYO knockdown at the transcriptomic and developmental levels. Moreover, differentiation is completely blocked when IYO and RIMA activities are simultaneously reduced and is synergistically accelerated when IYO and RIMA are concurrently overexpressed, confirming their functional interaction. Indeed, RIMA knockdown reduces the nuclear levels of IYO and prevents its prodifferentiation activity, supporting the conclusion that RIMA-dependent nuclear IYO accumulation triggers cell differentiation in Arabidopsis. Importantly, by analyzing the effect of the IYO/RIMA pathway on xylem pole pericycle cells, we provide compelling evidence reinforcing the view that the capacity for de novo organogenesis and regeneration from mature plant tissues can reside in stem cell reservoirs.